Concurrent training performed with and without repetitions to failure in older men: A randomized clinical trial. (22nd May 2019) - Teodoro, Juliana L.; da Silva, Larissa X. Neves; Fritsch, Carolina G.; Baroni, Bruno M.; Grazioli, Rafael; Boeno, Francesco P.; Lopez, Pedro; Gentil, Paulo; Bottaro, Martim; Pinto, Ronei S.; Izquierdo, Mikel; Cadore, Eduardo L.
Abstract : This study compared the effects of 20 weeks of concurrent training with and without repetitions to failure on neuromuscular and functional adaptations in older men. Methods: Thirty‐six older men (67.1 ± 5.1 years) were randomized into three groups: one performing repetitions to failure (RFG, n = 13), another performing repetitions not to failure and 50% of the repetitions of the RFG (NFG, n = 12), and a third performing repetitions not to failure with equal training volume of the RFG (ENFG, n = 11). Training was performed twice a week for 20 weeks at intensities ranging from 65% to 80% of maximal strength. In each session, the individuals started with strengthening exercises and then performed aerobic exercise on a treadmill. Before and after the intervention, individuals were assessed for their one repetition maximum (1RM) for leg press (LP) and knee extension (KE) exercises, knee extensors' isometric peak torque (PTiso ), and rate of torque development (RTD) at 50 ms, 100 ms, and 250 ms, muscle thickness of the quadriceps, as well as functional performance on sit‐to‐stand, and timed up and go tests. Results: After training, there were significant ( P < 0.001) increases in the LP and KE 1RM, PTiso, and RTD outcomes in all groups. Also, there were significant increases in muscle thickness of the quadriceps and in the sit‐to‐stand test ( P < 0.05) in all groups. No significant differences were observed between groups in any outcome. Conclusion: Concurrent training using repetitions to concentric failure did not promote additional benefits for neuromuscular function, muscle thickness, or functional capacity of older individuals.